Relationship between monocyte-to-lymphocyte ratio and anemia: a NHANES analysis - Yongjin Zhi; Shuojing Bao; Jingcheng Mao; Hui Zhu; Jianfeng Zhu (Hematology, 2025)
Background Growing evidence supports the significant role of inflammatory factors in anemia. This paper intends to ascertain the potential link between MLR and anemia and explore potential mediators.Methods Our analysis employed comprehensive data recourse from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018 utilizing weighted logistic regression models to assess the link between MLR and anemia. Restricted cubic spline analyses were implemented to evaluate MLR-anemia nonlinear relationship. Threshold effect analysis identified a critical inflection point. To ensure robustness, we conducted extensive subgroup analyses stratified by demographic and clinical factors. The mediating role of serum albumin on the link between MLR and anemia was investigated through mediation analysis.Results 28,616 participants were enrolled, with 2655 (9.28%) with anemia. After adjustment for all covariates, log2-transformed MLR (log2MLR) was linked with an enhanced risk of anemia (OR:1.49, 95%CI:1.33–1.65, P < 0.001). When log2MLR was categorized into quartiles, the trend remained consistent (P < 0.001). A nonlinear positive link was noted between log2MLR and anemia, with an inflection point at -2.812. No statistical interactions were unveiled in any subgroup analyses except for gender and diabetes (interaction P < 0.05). Interestingly, serum albumin partially mediated this association, accounting for 15.39% of the total effect.Conclusion This study presents groundbreaking findings on the role of MLR in anemia and the mediating effect of serum albumin, offering new perspectives on potential inflammatory pathways underlying hematological disorders.